2019
DOI: 10.1029/2019ja026631
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Winter Troughs' Position With Local Time, Longitude, and Solar Activity in the Northern and Southern Hemispheres

Abstract: Comprehensive pattern of ionospheric troughs' location in winter for all local times, longitudes, high (HSA), and low (LSA) solar activity, in both hemispheres, is at first investigated. Statistical analysis based on a large dataset of Interkosmos‐19, CHAMP, and Kosmos‐900 satellites was performed for quiet geomagnetic conditions Kp = 1–3. Three troughs were considered: high‐latitude trough (HLT) located inside the auroral oval, main ionospheric trough (MIT) located equatorward from the auroral oval, that is, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 45 publications
(114 reference statements)
5
20
0
Order By: Relevance
“…Moreover, He et al (2014) indicated that the narrow SAID channel moves equatorward during high solar activity periods. This is in agreement with that mentioned in Le et al (2017) and Karpachev (2019) that the position of midlatitude trough will move slightly equatorward from low solar activity to high solar activity periods. In our results, the SAPS‐related midlatitude trough exhibits almost identical percentile depletion among low and high solar activity periods.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, He et al (2014) indicated that the narrow SAID channel moves equatorward during high solar activity periods. This is in agreement with that mentioned in Le et al (2017) and Karpachev (2019) that the position of midlatitude trough will move slightly equatorward from low solar activity to high solar activity periods. In our results, the SAPS‐related midlatitude trough exhibits almost identical percentile depletion among low and high solar activity periods.…”
Section: Resultssupporting
confidence: 93%
“…The MIT is usually understood as a trough located equatorward of the auroral oval, i.e. it is a subauroral trough by definition 13 , 35 . This trough tracks, with a certain delay, variations in the Kp index according to the MIT model.…”
Section: Discussionmentioning
confidence: 99%
“…This model considers changes in the position of the MIT regarding Kp and local time. A recently revealed dependence on hemisphere 13 has also been considered. In Fig.…”
Section: Observation Datamentioning
confidence: 99%
“…The MIT is usually understood as a trough that is located equatorward of the auroral oval, i.e. it is a subauroral trough by de nition 13,35 . This trough tracks, with a certain delay, the variations in the Kp-index according to the MIT model.…”
Section: Resultsmentioning
confidence: 99%
“…This model takes into account the changes in the MIT position with Kp and local time. The recently revealed dependence on the hemisphere 13 , has been considered, too. In Fig.…”
Section: Observation Datamentioning
confidence: 99%